Numerical simulation of the long-term behaviour of a self-healing concrete beam vs standard reinforced concrete. (1st November 2015) - Hazelwood, T.; Jefferson, A.D.; Lark, R.J.; Gardner, D.R.
Highlights: A new model for a cementitious shape-memory-plastic material system is described. The model links beam elements for RC with axial elements for SMP tendons. SMP tendons are simulated using a transient thermo-mechanical approach. The model is successfully validated by comparison with experimental data. The material system can potentially reduce crack widths by up to 65%. Abstract: Research on the self-healing cementitious composite material system named LatConX is presented, with predictions made as to the effectiveness of the system in limiting crack widths in concrete beams subjected to sustained loads. A layered beam numerical model for the transient thermo-mechanical behaviour of reinforced concrete has been developed and coupled to a previously published numerical model for transient thermo-mechanical behaviour of a shape memory polymer. The combined model has been validated by comparison with experimental data. Finally, the model is used to predict ten-year crack widths in standard reinforced concrete beams, and in beams employing the LatConX system. These results indicate that the LatConX system has the potential to reduce crack widths by up to 65% when compared with an identical beam without the LatConX system.